2008
DOI: 10.4025/actascibiolsci.v30i3.377
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sampling methods for periphytic fauna in macrophytes at the Espinhaço Mountain Range Biosphere Reserve, Minas Gerais State, Brazil

Abstract: ABSTRACT. The methods "Jar", "Manual Removal" and "modified Ekman Dredge" were evaluated for sampling periphyton fauna associated with aquatic macrophytes. Sixty-three samples were collected from five lentic and three lotic water bodies at the Espinhaço Mountain Range Biosphere Reserve (Minas Gerais State, Brazil). Anova and Tukey statistical tests were performed for Protista, Rotifera and Crustacea richness, whereas the abundance of Protista, Rotifera, Crustacea, Gastrotricha, Tardigrada and Nematoda was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There are no standardized methods for collection of data in studies of microcrustacean fauna in wetlands, and different sampling techniques have been used (see Campbell et al, 1982;Sakuma et al, 2002;Ferreira et al, 2008;Loutte et al, 2008;Maia-Barbosa et al, 2008;Kruk et al, 2009). The usage of the same sampling method is an important strategy, since the lack of standardization in Table 1 for code names of the wetlands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no standardized methods for collection of data in studies of microcrustacean fauna in wetlands, and different sampling techniques have been used (see Campbell et al, 1982;Sakuma et al, 2002;Ferreira et al, 2008;Loutte et al, 2008;Maia-Barbosa et al, 2008;Kruk et al, 2009). The usage of the same sampling method is an important strategy, since the lack of standardization in Table 1 for code names of the wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…Sakuma et al (2002) suggested two methods based on sampling of submerged macrophytes using bottles to obtain the phytophilous fauna. Ferreira et al (2008) used three different methods to sample environments dominated by macrophytes (Jar, Manual Removal and Ekman Dredge) and concluded that the abundance and richness of the biota groups were dependent of the method used. Loutte et al (2008) used a sampler tube for the collecting cladocerans in dominated macrophytes ponds.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on freshwater nematodes are based on data collected only in a few countries, with scarce data concerning South America (Traunspurger et al, 2006). In Brazil, the few ecological studies on meiofauna and freshwater Nematoda have been conducted only in freshwater environments, such as lakes, lagoons, streams, reservoirs or rivers with no influence of tides (Ferreira et al, 2008;Lisboa et al, 2011;Flach et al, 2012;Meira et al, 2013;Netto and Fonseca, 2017;Pinto et al, 2021). An exception is Baia et al (2021), who studied Nematoda assemblages on an Amazon freshwater estuarine beach (environment subjected to tidal influence).…”
Section: Introductionmentioning
confidence: 99%